1998
DOI: 10.1159/000024520
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adhesion Factors and Degrading Proteins in Primary and Secondary Glioblastomas and Their Precursor Tumors

Abstract: In tumor tissue specimens of 27 primary and 17 secondary glioblastomas and the precursor lesions, the immunohistochemical expression patterns of the membrane protein CD44s, the basal lamina proteins laminin, collagen IV, and fibronectin, the lectin galectin-3 recognizing tenascin and N-CAM as well as of the matrix-degrading enzymes matrix metalloproteinase MMP-2 and MMP-9, and cathepsin D were studied. Besides expression of basal lamina proteins in vessels, all glioblastomas and the precursor lesions showed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 56 publications
(69 reference statements)
5
57
0
5
Order By: Relevance
“…4,13,14 However, when using archival frozen tissues (n ϭ 5 specimens) and formalin-fixed, paraffin-embedded blocks (n ϭ 21 specimens) from control brains, we were able to detect TN-C expression constantly in the ECM of the white matter, a finding that is consistent with recently published data by Tews and Nissen. 31 Based on these results, we conclude that, in the adult human brain, there still is a critical amount of total TN-C in the ECM of the white matter. This finding is highly important in the clinical setting, because it restricts systemic therapeutic approaches and forces us to develop highly specific MoAbs for radioimmunotherapy as applied in a locoregional therapeutic approach.…”
Section: The Normal Human Brainmentioning
confidence: 69%
“…4,13,14 However, when using archival frozen tissues (n ϭ 5 specimens) and formalin-fixed, paraffin-embedded blocks (n ϭ 21 specimens) from control brains, we were able to detect TN-C expression constantly in the ECM of the white matter, a finding that is consistent with recently published data by Tews and Nissen. 31 Based on these results, we conclude that, in the adult human brain, there still is a critical amount of total TN-C in the ECM of the white matter. This finding is highly important in the clinical setting, because it restricts systemic therapeutic approaches and forces us to develop highly specific MoAbs for radioimmunotherapy as applied in a locoregional therapeutic approach.…”
Section: The Normal Human Brainmentioning
confidence: 69%
“…In a recent study, activation of MVP (LRP) expression in glioblastomas has also been shown by immunohistochemistry. 21 Generally, the brain in humans 6 and rats 22 contains very low numbers of vaults. Only during late embryonic and early postnatal development of rats is intense vault immunostaining present in the microglia, which represents macrophage-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the biological mechanisms by which the high expression level of cathepsin D could affect the survival times of the patients with glioblastoma, the infiltrative areas of glioblastomas were examined with magnetic resonance imagings. Because cathepsin D takes part in degradation of the extracellular matrix and is strongly expressed by invading glioblastoma cells at the infiltrative margin (16), cathepsin D may be associated with the invasive nature of glioblastomas. Among the six patients with very high expression level of cathepsin D (R1.0), three manifested leptomeningeal disseminations on the Gdenhanced magnetic resonance imaging.…”
Section: Serum Cathepsin D In Glioma Patientsmentioning
confidence: 99%